Indoor Air Pollution due to Inadequate Ventilation and its Impact on Health among Children of Less Than Five Years in Eastern Nepal (Journal of Nobel Medical College, 2014)
Introduction: According to WHO, half of the developing world’s population depend on biomass (wood, dung and agricultural residues) and coal for such basic needs as cooking and heating. The smoke produced from the burning of these solid fuels on open fires or traditional stoves is referred to as indoor air pollution. IAP increases the risk of COPD and of acute respiratory illness in childhood, the most important cause of death among children less than 5 years of age in developing countries. Objectives: To find out the prevalence of IAP in terms of housing, overcrowding & ventilation. To assess the frequency, extent of biomass exposure and hazards on child health. Materials and methods: The cross sectional study was carried out in the Urban area of Katahari V.D.C. 4,6,7,8 for the duration of 6 months from February to August 2013 among 200 households. Lottery method was used to choose the wards and households. Data were analyzed using percentages, proportions and statistical test (chi-square test). Results: Due to excessive production of smoke and inadequate ventilation/chimney in the kitchen, such houses showed more prevalence of respiratory problems. Fifty percent of children were ill more than four times and 46% were seen at least twice. Almost all of them had experienced respiratory problems and 20% children were diagnosed with pneumonia in health facilities and treated. Ill ventilated kitchen, rooms along with dampness and absence of day light were the main factors contributing to the diseases comprising of 56%. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.10052 Journal of Nobel Medical College Vol.3(1) 2014; 35-39